2009
DOI: 10.1088/0953-8984/21/39/395503
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of elastic and stability properties of ZrC–ZrN and ZrC–TiC alloys

Abstract: Ab initio calculations of the elastic constants for several cubic ordered structures of zirconium carbonitride (ZrC(x)N(1-x)) and zirconium-titanium carbide (Zr(x)Ti(1-x)C) alloys were carried out. The calculations of total and formation energies, bulk modulus and elastic constants as functions of composition were performed with an ab initio pseudo-potential method. The predicted equilibrium lattice parameters are slightly higher than those found experimentally (on average by 0.2-0.4%). The predicted formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…The lattice parameter trends were similar to those observed for ZrC and ZrN. These results agreed well with results from other experimental and calculated results [7,8,29].…”
Section: Volume Expansion and Elastic Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…The lattice parameter trends were similar to those observed for ZrC and ZrN. These results agreed well with results from other experimental and calculated results [7,8,29].…”
Section: Volume Expansion and Elastic Propertiessupporting
confidence: 91%
“…In contrast, the shear and Young's moduli were influenced by whether the electrons were present in covalent bonds (metal d orbital-nonmetal p orbital bonds) or metallic bonds (metal d orbital-metal d orbital bonds). Our results regarding the elastic modulus of ZrC and ZrN are supported by previous calculation results [8,34].…”
Section: Volume Expansion and Elastic Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…1 shows the phase diagram of the TiCÀ ZrC system [12][13][14][15][16][17]. This system is a complete solid solution and has an immiscibility dome below 2400 K. The 90TiCÀ 10ZrC solid solution sintered at 2373 K had a uniform microstructure, and decomposed into two phases at the heat treatment temperature of 1573 K. This behavior was in good agreement with the phase diagram.…”
Section: Resultsmentioning
confidence: 62%
“…The TiC À ZrC system is a complete solid solution system, and we have demonstrated that 10 mol% ZrC can significantly enhance the sinterability of TiC À ZrC composites by forming homogeneous solid solutions [10,11]. On the other hand, it is known that the TiC À ZrC system is immiscible at temperatures lower than 2400 K. By heat treating the TiC À ZrC solid solution at a temperature lower than the consolute temperature, the solution decomposes into two phases and forms self-assembled nanoscale composites yielding high mechanical properties [12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%